Humanistic Approach as a Strategy for the Development of Islamic Religious Education Curriculum: Studies at MI Miftahul Ulum Toto Mulyo - Durotul Qoyimah; Tasman Hamami (Institut Agama Islam An-Nawawi Purworejo, 2025)
This study examines the application of a humanistic approach in the development of the Islamic Religious Education (PAI) curriculum in schools as an effort to realize more participatory, reflective, and experience-centered learning of students. The background of this research departs from the global need for religious education that not only conveys doctrine, but also humanizes students according to human values and Islamic teachings. International studies on humanistic religious education show this direction, while research in the Indonesian context is still limited and has not described the implementation of the curriculum comprehensively. This study uses qualitative methods through in-depth interviews, observations, and document analysis in schools that have implemented humanistic learning, with an interactive analysis process assisted by NVivo software for thematic coding. The findings of the study show a change from a teacher-centered learning pattern to learning that emphasizes dialogue, reflection, learning experiences, and personal interpretation of Islamic values. The humanistic approach is reflected in holistic learning objectives, the selection of contextual materials, learning strategies that involve the active participation of students, and authentic assessments that assess spiritual processes and development. This study concludes that the humanistic approach plays an important role in strengthening the relevance of the PAI curriculum to the needs of today's learners and the dynamics of modern education, although this study has limitations in the scope of location. Further studies are suggested to broaden the research context and assess the long-term impact of humanistic approaches on the spiritual and social development of learners in various educational settings.